2014
DOI: 10.3163/1536-5050.102.2.014
|View full text |Cite
|
Sign up to set email alerts
|

Measuring patrons' technology habits: an evidence-based approach to tailoring library services

Abstract: Librarians continually integrate new technologies into library services for health sciences students. Recently published data are lacking about student ownership of technological devices, awareness of new technologies, and interest in using devices and technologies to interact with the library. A survey was implemented at seven health sciences libraries to help answer these questions. Results show that librarian assumptions about awareness of technologies are not supported, and student interest in using new te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Wu et al [ 11 ] noted that students in medical programs possess a wide array of devices; thus, it is critical to continually monitor this information each year to better forecast future needs in related areas, such as libraries. Understanding students' attitudes, preferences, and the types of devices they use can help library staff remain flexible and ensure that timely resources are available for students.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al [ 11 ] noted that students in medical programs possess a wide array of devices; thus, it is critical to continually monitor this information each year to better forecast future needs in related areas, such as libraries. Understanding students' attitudes, preferences, and the types of devices they use can help library staff remain flexible and ensure that timely resources are available for students.…”
Section: Discussionmentioning
confidence: 99%
“…Social media, while an easy method to promote services and resources to a large audience, is problematic in terms of reaching an academic medical library's target audience. Not only does hospital IT frequently block access to social media sites for privacy and security reasons [11], students and staff are viewed as unlikely to follow the library on social media [13]. One respondent indicated that they felt resources were best reallocated elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…These labs may be run by the library, by campus IT, by university departments, or through partnerships between these entities. University technology services are often promoted on the web 1 , and some universities have applied assessment strategies such as pilot projects (Ray and Cook 2017) and surveys (Wu et al 2014). Design tools such as service blueprinting can be applied to further enhance assessment and innovation of technology services in libraries.…”
Section: Library Technology Servicesmentioning
confidence: 99%